The Dialectics of Nigerian Foreign Policy 1960-1966: Appraising the Dynamism of Neutrality in the Cold War Period - Amiara, Solomon Amiara (EBSU Journal of Social Sciences and Humanities, 2021)
Foreign Policy defines a state’s national interest abroad. The foreign policy of a state constitutes the essential elements that shape the state’s behaviour with another state. The Nigeria’s foreign policy between 1960-1966 had vacillated from non, alignment to total commitment to the West. The formulation of Nigeria’s foreign policy as a newly created state came at time the cold war between the East and West was at its peak. Therefore, this paper x-rays Nigeria’s foreign policy orientation, objectives and argued that Nigeria’s foreign policy despite her non-alignment posture was not indeed non aligned. Nigeria showed total commitment with the western led bloc and supported their influences with regard to conflict in Africa and in the World. This paper concluded that though Nigeria had in mind not to join any body but later changed stand to pay solidarity to the west.